A systematic review of public sector audits in Indonesia - Iis Istianah; Nia Pramita Sari; Indriani, Vitria (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2024)
The literature on public sector auditing in Indonesia remains nascent and requires further exploration. This study aims to provide a comprehensive overview and serve as a reference for future research in this field by analyzing the trends, developments, and prospects for further research on Indonesian public sector audit literature. This study uses a systematic literature review covering 36 articles from 2015 to 2022. It also highlights recent advancements and outlines recommendations for further research. Seven key categories for future research are identified: audit quality, audit findings and opinions, fraud, auditor characteristics, financial report quality, transparency and accountability, and emerging themes. The findings indicate that even while academic publications are on the rise, more thorough and diverse research is still required. The study indicates that research on public sector auditing in Indonesia is still in its infancy, with chances to investigate fraud, audit quality, audit findings and opinions, transparency, accountability, and emerging themes. This study's contribution is that it offers a thorough summary and a point of reference for upcoming investigations into public sector auditing in Indonesia.